Building Trust and Loyalty in Digital Marketplace: Determinants Influencing Online Customer in Pahang, Malaysia - Chen Wei, Yap; Shi Qing, Lim; Pee Shen, Soon; Wong Xin, Yi; Mohd Johan, Mohd Remie; Bahari, Noraine (UiTM Perlis, 2025)
In the era of digital advancements, the digital marketplace has transformed consumer behavior, fundamentally altering the landscape of online shopping and interaction. This research investigates the elements influencing customer loyalty toward the digital market, focusing on privacy and security, delivery options, ease of use, and promotional efforts. Drawing on data collected from 321 online marketplace customers in Pahang, Kuantan, the study examines the correlations between these factors and customer loyalty through a quantitative research approach. Results indicate strong positive relationships between privacy and security measures, delivery service, user-friendly interfaces, promotions, and customer loyalty. Specifically, robust privacy and security protocols, efficient delivery service, intuitive interfaces, and targeted promotions significantly enhance customer loyalty in the digital marketplace.